Rancang Bangun Alat Pemanas Induksi Proses Perlakuan Panas - Ipung Kurniawan; Bayu Aji Girawan; Imam Muasih; Yosep Susanto (Accurate: Journal of Mechanical Engineering and Science, 2020)
The heat treatment process using the fuel system is very numerous and the heating time is quite long. The use of induction heaters, heat treatment can be done with a shorter time and less energy. The purpose of this research are; (1) Make a plan design, (2) Measure the part of machine element, (3) Measure the estimation of time and design budget, (4) Test the result of induction heater machine. The method in this study uses experimental. The result of concept design evaluation, i.e., the use of trapezoid screw on the lifter system was 0,2 kilowatt of motor power, 12 mm of shaft diameter, and ball bearing 6201 with the age of 0,31 years which determined from the calculation of machine element on the induction heater system. The total of time for making this machine was 3.182,06 minutes and it spent Rp 5.360.700,-. The result of test shows that the hardness rate of raw material mild steel that given heat of hardening temperature of 850 0C, that endured for 45 minutes increasing being 84,3 HRB. However, after being tempered temperature of 400 0C having a decrease being 69 HRB.